How to Simplify the Diagnostic Criteria of Metabolic Syndrome in Adolescents - Chun-Ming Ma; Fu-Zai Yin; Xiao-Li Liu; Rui Wang; Dong-Hui Lou; Qiang Lu (Elsevier, 2017)
This study evaluated the feasibility and accuracy of the height-corrected definition for identifying metabolic syndrome (MS). Methods: In 2006, anthropometric and biochemical measurements were assessed in a cross-sectional population-based study of 3136 Han adolescents, aged 13-17 years. MS was defined according to the definitions of Cook et al, International Diabetes Federation, and the Society of Pediatrics, Chinese Medical Association. Waist-to-height and blood pressure-to-height ratios were alternatives to waist circumference and blood pressure in the height-corrected definition. Results: According to the MS definition and the height-corrected MS definition, this agreement would be classified as "very good" (National Cholesterol Education Program kappa coefficients: 0.850 in boys and 0.816 in girls; International Diabetes Federation kappa coefficients: 0.953 in boys and 0.807 in girls; Society of Pediatrics, Chinese Medical Association kappa coefficients: 0.932 in boys; p < 0.001) and "good" (Society of Pediatrics, Chinese Medical Association kappa coefficients: 0.737 in girls; p < 0.001). Conclusion: The present study demonstrates that the height-corrected definition of MS is a simple, inexpensive, and accurate tool for identifying MS in Han adolescents.